Social Work and Women's Mental Health: Does Trauma Theory Provide a Useful Framework?. (30th October 2018) - Tseris, Emma
Abstract: Trauma theory has been positioned as a helpful framework for social workers to utilise when working with women presenting to mental health services. In particular, the trauma concept has been praised for its ability to acknowledge the social and relational determinants of women's mental health presentations and to challenge the dominance of a biomedical framework for understanding emotional distress. On the other hand, trauma approaches have been critiqued for being overly deficit-oriented and for failing to adequately incorporate a feminist analysis of gender inequality. This article presents qualitative research conducted with twelve mental health social workers in Australia reporting on their use of trauma theory when working with adolescent women who have experienced child abuse within a family context. Analysis found that the trauma concept was in some cases applied in a paternalistic manner that medicalised young women's distress and minimised issues of gender inequality. However, other participants described trauma work with young women as a form of feminist activism. This study is significant because it points towards the existence of multiple and competing trauma perspectives currently informing social work practice.